How are schools implementing a universal social–emotional learning program? Macro- and school-level factors associated with implementation approach - Thierry, Karen L.; Page, Amanda; Currie, Cailin; Posamentier, Jordan; Liu, Yangyang; Choi, Jane; Randall, Haleigh; Rajanbabu, Poojashree; Kim, Tia E.; Widen, Sherri C. (Frontiers in Education, 2022)
Introduction For universal SEL programs to contribute to positive learning environments, all school staff must be involved in implementing the program (CASEL, 2020). The first aim of the current study was to examined school/district- and macro-level factors associated with two approaches to SEL program implementation observed in schools: (1) classroom teachers as instructors of SEL lessons (i.e., teacher-facilitated) or (2) school counselors as instructors of SEL lessons (i.e., counselor-facilitated). A second aim was to examine the SEL provider’s perception of the context of counselor-facilitated implementation in schools. Methods Public elementary and middle schools in the U.S. (N = 6,657), that adopted the Second Step digital program in the 2021-22 school year, were identified as utilizing teacher- or counselor-facilitated implementation using usage records. Predictor variables, namely support for SEL (i.e., state plans to utilize federal funding for SEL programs or access to systemic SEL consultation) and state adoption of stand-along K-12 SEL standards/competencies, were obtained from publicly available data sources. To evaluate the second aim, interviews were conducted with Second Step client support staff (N = 5), each representing hundreds of schools utilizing a counselor-facilitated implementation approach. Results A Generalized Linear Mixed Model analysis indicated that schools in states with support for SEL (i.e., plans to utilize federal funding for SEL programs or access to systemic SEL consultation) were more likely to use teacher-facilitated implementation than schools without support (OR = 1.64, p < .01, CI = 1.15 – 2.34). Schools in states that were early adopters of stand-alone K-12 SEL standards/competencies tended to be more likely than those without K-12 SEL standards/competencies to use teacher-facilitated implementation (OR = 1.70, p = .06, CI = 1.00 – 2.95). A qualitative study involving iInterviews with Second Step staff who support hundreds of schools utilizing counselor-facilitated implementation identified other potential factors motivating counselors as facilitators, including low SEL buy-in and limited staff capacity. Although this approach has challenges, it could be a pathway to teacher-facilitated implementation over time. Discussion Taken together, findings indicate promising strategies for the promotion of more schoolwide use of SEL programs.